Swiss Medical Devices for Autologous Regenerative Medicine: From Innovation to Clinical Validation - Farid Gomri; Solange Vischer; Antoine Turzi; Sarah Berndt (MDPI AG, 2022)
Regenerative medicine, based on the use of autologous tissues and embryonic, stem or differentiated cells, is gaining growing interest. However, their preparation, in a manner compliant with good practices and health regulations, is a technical challenge. The aim of this manuscript is to present the design of reliable CE marked medical devices for the preparation of standardized platelet-rich plasma (PRP) and other autologous biologics intended for therapeutic uses. There are numerous PRP isolation processes. Depending on the methodology used, PRP composition varies greatly in terms of platelet concentration, platelet quality, and level of contamination with red and white blood cells. This variability in PRP composition might affect the clinical outcomes. The devices presented here are based on a specific technology, patented all over the world, that allows the precise separation of blood components as a function of their density using thixotropic separator gels in closed systems. This allows the preparation, in an automated manner, of leukocyte poor PRP with a standardized composition. Production of different forms of PRP is a clinical asset to suit various therapeutic needs. Therefore, we are offering solutions to prepare PRP either in liquid or gel form, and PRP combined with hyaluronic acid. These biologics have been successfully used in many different therapeutic domains, resulting in more than 150 published clinical studies. We also developed the CuteCell technology platform for cell culture expansion for further autologous cell therapies. This technology enables the safe and rapid in vitro expansion of cells intended for therapeutic use in good manufacturing practices (GMP) and autologous conditions, using blood-derived products as culture media supplementation. We summarize in this article our 20 years' experience of research and development for the design of PRP devices and, more recently, for PRP combined with hyaluronic acid.